Passively mode-locked Er3+ and Tm3+-doped fiber lasers by using a common gold nanorods/D-shaped fiber as saturable absorber. (23rd October 2020) - Cui, Linghao; Liu, Jiaxing; Li, Nan; Wang, Fang; Jia, Zhixu; Kang, Zhe; Qin, Weiping; Qin, Guanshi
Abstract: We demonstrate passively mode-locked erbium/thulium doped fiber lasers (TDFLs) operating at 1560/1950 nm by using a common gold nanorods (GNRs)/D-shaped fiber as saturable absorber (SA). The SA is prepared by the composite of GNRs with an average aspect ratio of 5.3 and D-shaped fiber, which has broadband absorption from 1000 nm to 3000 nm. By inserting the same SA into an erbium or thulium doped fiber laser cavity, stable passively mode-locked laser at 1560 or 1950 nm is achieved, respectively. A 1560 nm laser with a pulse width of 590 fs and a repetition frequency of 25.72 MHz is obtained for the erbium doped fiber laser (EDFL), and a 1950 nm laser with a pulse width of 373 fs and a repetition rate of 27.66 MHz is also obtained for the TDFL. Our results show that the GNRs/D-shaped fiber SA could be used for constructing broadband femtosecond fiber lasers.